HSP90 inhibitor, DMAG, synergizes with radiation of lung cancer cells by interfering with base excision and ATM-mediated DNA repair - Thuy T. Koll; Steven S. Feis; Mollie H. Wright; Modupe M. Teniola; Mekel M. Richardson; Ana I. Robles; John Bradsher; Jacek Capala; Lyuba Varticovski (2008)
Abstract Inhibition of heat shock protein 90 (HSP90) leads to inappropriate processing of proteins involved in cell survival pathways. We found that HSP90 inhibitor, 17-(dimethylaminoethylamino)-17-demethoxygeldanamycin (DMAG), is synergistic with radiation for non-small cell lung cancer cell lines, NCI-H460 and A549. To establish the optimal schedule for this combination, cells were radiated before, after, or simultaneously with DMAG, and survival was scored by clonogenic assay. The sequence of DMAG administration was critical for synergy with radiation, and pretreatment for 16 h led to maximal synergy. Similar radiosensitization was observed in isogenic cells in which expression of wild-type p53 was silenced by RNA interference, although p53 loss rendered cells overall less radiosensitive. The mechanistic basis for synergy was studied by Western blotting, cell cycle analysis, alkaline comet assay, and direct measurement of the activities of key base excision repair enzymes. Regardless of schedule of administration, DMAG led to degradation of proteins involved in activation of cell survival pathways after radiation, which did not explain the differences in the schedule of administration observed in clonogenic assays. In addition to previously reported decrease in activation of ATM, pretreatment with DMAG blocked activation of base excision repair machinery and activity of key enzymes, apurinic/apyrimidinic endonuclease, and DNA polymerase-β. Similarly, pretreatment with specific apurinic/apyrimidinic endonuclease inhibitor, CRT0044876, reproduced the effects of DMAG. Thus, administration of HSP90 inhibitors before radiation is critical for optimizing their use as radiosensitizers. [Mol Cancer Ther 2008;7(7):1985–92]